Characterising electrosprayed biomolecules using tandem-MS - the noncovalent GroEL chaperonin assembly - Sobott, F; Robinson, C (2004)
It is now possible to transfer large protein complexes intact into the gas phase using nano-electrospray ionisation (ESI) and to investigate their stoichiometry in a mass spectrometer. Using as a model assembly the noncovalent 14mer (ca. 800 kDa) of the chaperonin GroEL from Escherichia coli we show that the measured mass of the assembly is higher than expected from the sum of the components and explore parameters of ion activation that affect this 'noncovalent mass shift'. Under optimal desolvation conditions the measured mass is ∼0.5% greater than the calculated value indicating that part of the solution environment remains attached to these ions during phase transfer. The origin of this noncovalent mass shift is explored using tandem mass spectrometry experiments. Collisional activation of the 65+ charge state of the GroEL 14mer indicates the presence of up to 100 solvent/buffer molecules, both positively and negatively charged, which are stripped during CID in the gas-filled collision cell. At high collision energies, asymmetric dissociation into highly charged monomer and 13mer complexes takes place revealing the subunit composition of the assembly. Under these conditions the noncovalent mass shift is significantly reduced (<0.04%) demonstrating the utility of this tandem approach for mass measurement of biomolecules in the gas phase. © 2004 Elsevier B.V. All rights reserved.